Transcriptome and physiology analysis reveal key players of the shade-tolerant species Panax notoginseng in photosynthetic performance under both high and low light regimes. Issue 1 (31st December 2022) - Zhang, Jin-Yan; Kuang, Shuang-Bian; Cun, Zhu; Shuang, Sheng-Pu; Meng, Zhen-Gui; Li, Long-Gen; Chen, Jun-Wen
ABSTRACT: The present study aimed to understand the molecular mechanism underlying the light-induced depression of photosynthetic capacity in a typically shade-tolerant species Panax notoginseng grown under different light intensities. Photosynthetic performance was declined in the low-light- and high-light-grown plants. The physiological plasticity was low, while the plasticity of morpho-anatomy traits, biomass allocation and biochemical traits was great in response to the light environment. High light enhanced the expression of genes related to reactive oxygen scavenging, pentose phosphate pathway and glycolysis. The expression of genes involved in the light reaction was suppressed in low light, along with a reduction in Rubisco activity. The expression of genes encoding Rubisco was repressed in high light. Photosynthetic capacity in low light might be inhibited by the deceleration on light reaction and by the increase of inactivated Rubisco, high-light-induced decrease of photosynthetic performance might result from the deceleration on Calvin cycle. Abbreviations: A net, net assimilation rate; LCP, light compensation point; PQ, plastoquinone pool; LSP, light saturation point; PPFD, photosynthetic photon flux density; C i, internal leaf CO2 concentration; A max, maximum net photosynthesis rate; CE, carboxylation efficiency; J max, maximum electron transfer rate; V cmax, maximum carboxylation efficiency; R d, dark respiration rate; F v / F m, maximum quantum yield of photosystem II; ΦPSII, PSII photochemical quantum yield; qP, photochemical quenching; F v ′/ F m ′, photochemical efficiency of PSII in the light; NPQ, non-photochemical quenching; Φ f.d, fluorescence quenching dissipation; Φ NPQ, non-photochemical quenching dissipation; (V + A+Z), the xanthophyll cycle pigment pool; L, lutein; N, neoxanthin; β-Car, β-Carotene; SOD, superoxide dismutase; CAT, catalase; POD, peroxidase; APX, ascorbate peroxidase; MDHAR, monodehydroascorbate reductase; DHAR, dehydroascorbate reductase